Nile Breweries leverages CCAFS Guide to Assessing Climate Resilience in Smallholder Supply Chains to improve the resilience of 20,000 barely and sorghum farmers in Uganda - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Nile Breweries Limited, a subsidiary of AB InBev, has sought to improve their supply chains of sorghum and barley through local sourcing and sustainability commitments. As part of the USAID Feed the Future Learning Community for Supply Chain Resilience, Nile Breweries Limited partnered with TechnoServe and the Sustainable Food Lab to assess climate Resilience in smallholder supply chains to understand their climate risks and the interventions available to build resilience of sorghum and barley farmers.